A CRITICAL REVIEW OF THE CURRENT CHECKLIST OF BUTTERFLIES OF SERBIA - Jakšić, Predrag (Bulletin of Natural Sciences Research, 2019)
The latest checklist of butterflies of Serbia (Papilionoidea Latreille, 1802) by Popović & Verovnik (2018) is examined. In consistencies with regard to the cited literature and applied systematics are pointed out. The validity of the viewpoints of the above mentioned authors on the species Leptidea juvernica Williams, 1946, Pyrgus trebevicensis (Warren, 1926), Erebia manto (Denis Schiffermüller, 1775) and Melitaea ornata Christoph, 1893 is discussed. It is shown that by imposing new Serbian names to butterflies disregards national and scientific heritage.
Keywords: Butterflies; Papilionoidea; Republic of Serbia